2022
DOI: 10.1073/pnas.2109255118
|View full text |Cite
|
Sign up to set email alerts
|

A genetic switch for male UV iridescence in an incipient species pair of sulphur butterflies

Abstract: Mating cues evolve rapidly and can contribute to species formation and maintenance. However, little is known about how sexual signals diverge and how this variation integrates with other barrier loci to shape the genomic landscape of reproductive isolation. Here, we elucidate the genetic basis of ultraviolet (UV) iridescence, a courtship signal that differentiates the males of Colias eurytheme butterflies from a sister species, allowing females to avoid costly heterospecific matings. Anthropogenic range expans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 61 publications
0
47
0
Order By: Relevance
“…Since male wood tiger moths, which are actively searching for females in the vegetation, have limited ability to see differences in yellow‐orange‐red hues (Henze et al, 2018), it is unlikely that sexual selection alone would be responsible for the colouration of females, but we cannot exclude the possibility that male colouration could be used in intraspecific communication. Moreover, recent studies in other species have shown that UV may facilitate separation of incipient species as recently demonstrated in Colias butterflies (Ficarrotta et al, 2022) and that the differences in UV reflection may arise from novel duplication of the gene producing sex‐specific differences in reflectance as in Zerene cesonia butterfly (Rodriguez‐Caro et al, 2021). Previous experiments have shown that birds learn to avoid red wood tiger moths more effectively than yellow or white ones (Ham et al, 2006; Lindstedt et al, 2011; Rönkä et al, 2018), but the selection for visual signals may be altered due to multimodal signalling (Rojas et al, 2018; Winters et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…Since male wood tiger moths, which are actively searching for females in the vegetation, have limited ability to see differences in yellow‐orange‐red hues (Henze et al, 2018), it is unlikely that sexual selection alone would be responsible for the colouration of females, but we cannot exclude the possibility that male colouration could be used in intraspecific communication. Moreover, recent studies in other species have shown that UV may facilitate separation of incipient species as recently demonstrated in Colias butterflies (Ficarrotta et al, 2022) and that the differences in UV reflection may arise from novel duplication of the gene producing sex‐specific differences in reflectance as in Zerene cesonia butterfly (Rodriguez‐Caro et al, 2021). Previous experiments have shown that birds learn to avoid red wood tiger moths more effectively than yellow or white ones (Ham et al, 2006; Lindstedt et al, 2011; Rönkä et al, 2018), but the selection for visual signals may be altered due to multimodal signalling (Rojas et al, 2018; Winters et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…Here we show that a number of wing patterning genes are differentially expressed in the brain and eyes during a sexual (training) encounter. Not only are these genes associated with wing patterning in a range of butterfly species, but a subset of these genes are specifically associated with aspects of eyespot production in B. anynana (Brunetti et al, 2001; Ozsu and Monteiro, 2017; Prakash and Monteiro, 2018) and/or with UV reflectance (Ficarrotta et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we used the functional annotations and butterfly wing patterning gene list from Ernst and Westerman (2021) to identify wing patterning genes expressed in eye and brain tissue and to determine if they were differentially expressed between the sexes. The genes included numerous B. anynana wing patterning genes (Beldade and Peralta, 2017; Bhardwaj et al, 2018; Connahs et al, 2019; Matsuoka and Monteiro, 2018; Monteiro et al, 2013; Monteiro et al, 2006; Monteiro and Prudic, 2010; Ozsu et al, 2017; Prakash and Monteiro, 2018, 2020; Saenko et al, 2011), as well as genes characterized in other butterfly species (Ficarrotta et al, 2022; Martin and Reed, 2010; Nadeau et al, 2016; Reed et al, 2011; Westerman et al, 2018; Woronik et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This last function of the gene appears to be connected to changes in the first intron of the bab gene, which may contain a CRE regulating a smaller sub‐set of this gene's functions. Evolution of male‐specific abdominal pigmentation in D. melanogaster (Williams et al, 2008), of male specific UV‐iridescence patterns in Colias eurytheme (Ficarrotta et al, 2021), and of asymmetric male preference towards different female pheromones in the European corn moth, Ostrinia nubilalis , all involve changes in this intron (Ficarrotta et al, 2021, Unbehend et al, 2021, Williams et al, 2008).…”
Section: Evolution Of Enhancer Modularity and Hotspot Locimentioning
confidence: 99%
“…A different gene, bric‐a‐brac ( bab ), has also been proposed as a hotspot locus for the evolution of male‐specific traits. The gene plays a role in pattern formation along the proximal‐distal axis of legs and antennae, and in specifying male‐specific traits in lepidopterans and flies (Ficarrotta et al, 2021, Unbehend et al, 2021, Williams et al, 2008). This last function of the gene appears to be connected to changes in the first intron of the bab gene, which may contain a CRE regulating a smaller sub‐set of this gene's functions.…”
Section: Evolution Of Enhancer Modularity and Hotspot Locimentioning
confidence: 99%